Oltre il confine della domus: Giulia maggiore e altre donne romane negli spazi urbani e in viaggio - Rita Degl’Innocenti Pierini (Storia delle Donne)
This paper aims at investigating a particular variant of the concept of boundary relatively to the world of Roman women. For them the limen, the threshold of their house, is ideally and culturally their limes, the boundary beyond which their action can no longer be free, but is controlled according to precise ethical canons that prevent women from participating in political life or moving freely outside the Urbs. Through the analysis of literary texts of the Republican and Augustan ages and beyond, locutions such as limen, domi, intra vs. extra, ultra, clearly mark this marginality imposed by mos maiorum. A transgression of such limits implies an abdication of the main traditional female values, such as modesty and decency, and therefore damages the honour of women. The point is exemplified by the case of Giulia major exiled by her father Augustus with a public accusation of immoral behaviour.